PITUITARY HYPERPLASIA SECONDARY TO PRIMARY HYPOTHYROIDISM – A CASE REPORT - Abdulla, Nurul Asyiqin; Noordin, Mazidah; Nor, Noor Shafina Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Primary hypothyroidism in children can present insidiously and mimic other systemic conditions, including neurological symptoms. In rare cases, it may lead to pituitary hyperplasia due to lack of negative feedback on thyrotrophs. Timely recognition is essential to prevent complications and avoid unnecessary neurosurgical intervention. CASE We report a case of an 8-year-old female who presented with chronic headaches, cold intolerance, constipation and frontal scalp hair thinning. Symptoms were insidious, with persistent headaches noted since the age of six. Despite multiple outpatient visits, including private pediatric and ophthalmology consultations, no clear diagnosis was made. Ophthalmological evaluations were also normal. Due to persistent symptoms, neuroimaging was done to exclude intracranial mass or raised intracranial pressure. MRI of the brain and pituitary revealed enlarged pituitary gland measuring 7.7 mm (AP) x 12.4 mm (width) x 9.7 mm (height), with normal posterior pituitary bright spot and pituitary stalk. Other surrounding structures were normal. Thyroid function test (TFT) performed revealed an elevated TSH of 150 mIU/L with low fT4 at 8.7 pmol/L, consistent with primary hypothyroidism. Anti-thyroid peroxidase (TPO) and thyroglobulin antibodies were positive, confirming Hashimoto’s thyroiditis. Other pituitary hormones were normal. She was initiated on levothyroxine, and serial TFTs demonstrated gradual improvement. MRI features were consistent with pituitary hyperplasia secondary to long-standing hypothyroidism (PHPH), and no neurosurgical intervention was warranted. A repeat MRI scan performed 10 months after commencement of treatment showed normal study with a pituitary gland measuring 6.7 mm (AP) x 12.2 mm (width) x 5.7 mm (height). Her latest TFT has normalised with TSH of 3.76 mIU/L and fT4 of 18.5 pmol/L on levothyroxine 37.5 mcg qd Monday to Friday, and 50 mcg qd on weekends. CONCLUSION PHPH is an uncommon cause of pituitary enlargement in children. This case highlights the importance of comprehensive endocrine assessment in children with chronic headaches. Early diagnosis and thyroid hormone replacement can lead to complete resolution of symptoms and regression of pituitary enlargement, avoiding misdiagnosis and overtreatment.